Comparative evaluation of shaping ability of sequential rotary, single rotary, and single reciprocating file systems in simulated curved canals using cone-beam computed tomography: An in vitro study - P Senthamil Selvan; R V Aparajitha; A Shafie Ahamed; S Bhavani; G Rajaraman (Wolters Kluwer Medknow Publications, 2022)
Aim: The purpose of the study was to evaluate and compare canal transportation (CT) and centering ability (CA) between sequential rotary, single rotary, and single reciprocating file systems using cone-beam computed tomography (CBCT) in simulated curved canals. Materials and Methods: Thirty curved root canals simulated in clear resin blocks were divided randomly into three groups - Group I - ProTaper Gold-PTG (Sequential continuous rotation), Group II - One Curve-OC (Single-file continuous rotation), and Group III - WaveOne GOLD-WOGs (Single-file reciprocating motion) Ten samples of each group were positioned in a custom-made dental stone holder and subjected to CBCT scanning with 5 samples at a time at 3 mm, 5 mm, and 7 mm from the apical end before and after instrumentation. The canals were subjected to instrumentation using the files according to the group allotted. The files were used as recommended by the manufacturer and subjected to CBCT scanning. The values of CT and CA were obtained using the formula given by Gambill et al., and statistical analysis was performed. Results: The results showed that within the groups, all groups showed higher mean values of CT and lower CA in apical level followed by middle and coronal level, respectively, and between the groups, the least CT and highest CA exhibited in WOG followed by OC and PTG, respectively. Conclusion: The least CT and highest CA exhibited in WOG (Single-file reciprocation system) followed by OC (Single-file continuous rotation) and PTG (Sequential file system with continuous rotation), respectively.